Decisional Balance of Smoking and Planning to Quit Smoking: A Moderated Mediation Model among Chinese Male Smokers. Issue 2 (15th March 2022) - Cao, Ningmeng; Li, Xinwei; Chen, Haide; Li, Xinyu; Li, Weijian
ABSTRACT: Decisional balance in quitting smoking involves positive and negative attitudes toward smoking. This study explored the relationship between the decisional balance of smoking and planning to quit smoking, and examined the mediating role of willingness to quit smoking and the moderating role of social support. A questionnaire survey was conducted among 326 daily male smokers from China in 2016, including the decisional balance of smoking, willingness to quit smoking, social support, planning to quit, and nicotine dependence. The results showed: (1) willingness to quit smoking mediated the relationship between the decisional balance of smoking and planning to quit smoking; (2) the relationship between the decisional balance of smoking and planning to quit smoking was moderated by emotional support rather than instrumental support. Smokers with a higher level of emotional support for quitting smoking were more likely to progress to planning to quit smoking, while this relationship was not found among smokers with a lower level of emotional support. These findings suggested that smokers' willingness to quit smoking would be key to promoting their planning to quit. Meanwhile, the dynamic process of planning to quit smoking was moderated by emotional support from others.